WHY IS ETHICS NECESSARY IN BUSINESS ? - Marjam Desma Rahadhini, Ira Nuriya Santi & (PROCEEDING INTERNASIONAL SEMINAR, 2015)
Ethics plays an important role in a business. The existence of ethics is expected to be a barometer measuring moral values, especially policies resulting in business. The policy is expected not to harm the public who serve as the spearheading of a business. This paper aims to examine the reasons why business ethics must be done by a business enterprise. Descriptively this paper explains that it is necessary for a business enterprise to apply business ethics as a tool or weapon to compete with its competitors. A company running an ethical business will be able to maintain its viability in the long term.Keywords: business ethics, competitiveness, and public policy